Electrochemical Arylation of Electron‐Deficient Arenes through Reductive Activation. (17th September 2019) - Wang, Pan; Yang, Zhenlin; Wang, Ziwei; Xu, Chenyang; Huang, Lei; Wang, Shengchun; Zhang, Heng; Lei, Aiwen
Abstract: An electrochemical method has been developed to achieve arylation of electron‐deficient arenes through reductive activation. Various electron‐deficient arenes and aryldiazonium tetrafluoroborates are amenable to this transformation within the conditions of an undivided cell, providing the desired products in up to 92 % yield. Instead of preparing diazonium reagents, these reactions can begin from anilines, and they can be carried out in one pot. Electron paramagnetic resonance studies indicate that cathodic reduction of quinoxaline occurs using the transformation. Moreover, cyclic voltammetry indicates that both quinoxaline and aryl diazonium salt have relatively low reduction potentials, which suggests they can be activated through reduction during the reaction. Abstract : Eine elektrochemische Methode wurde entwickelt, um elektronenarme Arene durch reduktive Aktivierung zu arylieren. Für diese Transformation wurden verschiedene elektronenarme Arene und Aryldiazonium‐Tetrafluoroborate in einer ungeteilten Zelle untersucht, wobei die gewünschten Produkte in Ausbeuten bis zu 92 % erhalten wurden. Die Reduktion von Chinoxalin ist ein wichtiger Schritt der Transformation.